Influential role of lean soft tissue in the association between training volume and bone mineral density among male adolescent practitioners of impact-loading sports: ABCD Growth study - Narciso, Pedro Henrique [UNESP]; Werneck, André Oliveira; Luiz-de-Marco, Rafael [UNESP]; Ventura Faustino-da-Silva, Yuri da Silva [UNESP]; Maillane-Vanegas, Santiago [UNESP]; Agostinete, Ricardo Ribeiro [UNESP]; Fernandes, Rômulo Araújo [UNESP] (My University, 2020)
Background: Training volume is associated with direct and indirect pathways of bone adaptations. In addition, training volume is a training variable associated with lean soft tissue (LST), which has been shown to be an important predictor of areal bone mineral density (aBMD). Thus, the aim of this study is to investigate the influential role of lean soft tissue (LST) in the association between training volume and aBMD in male adolescent athletes. Methods: This cross-sectional study was composed of 299 male adolescent athletes, mean age 14.1 (1.8) years, from 9 different weight-bearing modalities. The Ethical Board approved the investigation. The adolescents reported the number of days per week they trained and the time spent training and, from this, the training volume (h/wk) was estimated. The LST and aBMD were assessed by dual-energy x-ray absorptiometry. Somatic maturation was estimated by the peak of height velocity. Mediation analysis was performed to investigate the role of LST in the association between training volume and aBMD. Level of significance was set at p < 0.05. Results: LST partially explained the association between training volume and aBMD in all body segments: upper limbs (58.37%; β = 0.00142), lower limbs (28.35%; β = 0.00156), spine (33.80%; β = 0.00124), and whole body (41.82%, β = 0.00131). There was no direct effect of training volume on aBMD in upper limbs (CI -0.00085 to 0.00287). Conclusion: The association between training volume and aBMD is influenced by LST in different body segments, mainly upper limbs, demonstrating that interventions aiming to enhance aBMD should also consider LST as an important variable to be managed.
Keywords: body composition; bone tissue; muscle mass